Solution of Black-Scholes Equation on Barrier Option (Journal of Informatics and Mathematical Sciences, 2017)
In this article, a solution of the Black-Scholes partial differential equation corresponding to barrier options is proposed. Semigroup theory techniques and Mellin transform method are used to discuss its solution.
Keywords: European option; Barrier option; Black Scholes equation; Co-semigroups; Mellin transform